A safe agricultural space for biodiversity - García-Vega, Diego; Dumas, Patrice; Prudhomme, Rémi; Kremen, Claire; Aubert, Pierre-Marie (Frontiers in Sustainable Food Systems, 2024)
Agriculture is the main driver of the rapid collapse of biodiversity, upon which all life on Earth, including agricultural production, depends. As we face the challenge of feeding a growing human population under a changing climate regime, the pressure on biodiversity is expected to further intensify. While the potential to expand and improve natural habitats for biodiversity conservation has been widely explored in large-scale scenarios of agricultural systems, the critical role of agricultural landscapes' management on halting the loss of biodiversity remains unexplored at this scale. We argue that, to achieve an effective conservation of biodiversity (both natural and agricultural), the combined multivariate effects of agriculture on biodiversity must be accounted for, including its surface area as well as its management. Based on a literature review, we identified the main biodiversity pressures stemming from agriculture: landuse change, contribution to climate change, water withdrawal, pesticide pollution, nutrient (nitrogen and phosphorus) pollution, and landscape and farm-scale simplification (of croplands and pastures). For each one, we proposed a critical boundary, based on reviews of studies covering a range of taxa, biodiversity metrics, and biomes, below or above which negative impacts on biodiversity are minimized or positive effects arise. Implemented simultaneously, the identified boundaries would integrate biodiversity conservation within and across farmlands and minimize agriculture's far-reaching impacts on biodiversity. We present a framework called "agricultural boundaries for biodiversity" that will allow to explore the potential of developing agricultural systems that effectively reconcile food production and biodiversity conservation at large scales.